A Two‐Dimensional Iron(II) Coordination Polymer with Synergetic Spin‐Crossover and Luminescent Properties. (20th May 2019) - Ge, Jing‐Yuan; Chen, Zhongyan; Zhang, Li; Liang, Xiao; Su, Jian; Kurmoo, Mohamedally; Zuo, Jing‐Lin
Abstract: A composite material, {[Fe(L)(TPPE)0.5 ]⋅3 CH3 OH} n, has been constructed by integrating the spin‐crossover (SCO) subunit Fe II {diethyl(E, E)‐2, 2′‐[1, 2‐phenyl‐bis(iminomethylidyne)]bis(3‐oxobutanoate)‐(2‐)‐N, N′, O 3, O 3 ′} and the highly luminescent connector 1, 1, 2, 2‐tetrakis(4‐(pyridin‐4‐yl)phenyl)‐ethene. Its structure contains four staggered 4×4 layers and intercalated methanol. The packing is dominated by considerable H‐bonds either between adjacent layers and between layers and guests. A crystal‐structure transformation was detected upon removal of the guest molecules. The SCO transition of the solvated crystals is centered at ca. 215 K with a non‐symmetrical hysteresis of 25 K wide, and the desolvated [Fe(L)(TPPE)0.5 ] n exhibits gradual SCO without hysteresis. Intriguingly, the intensity of the fluorescence at 460 nm for the latter is maximized at the SCO transition. The energy transfer between luminescent and SCO entities is achievable as confirmed by theoretical calculations. Abstract : Schaltbares Material : Ein Fe II ‐Koordinationspolymer mit Quadratgitterschichten beruht auf dem Luminophor‐Konnektor TPPE. Dieses Gerüst zeigt nicht nur lösungsmittelabhängiges Struktur‐ und Spin‐Crossover(SCO)‐Verhalten, sondern auch ein Schalten zwischen Spinübergang und Fluoreszenz für die gastfreie Spezies. Theoretischen Studien zufolge liegt ein Energietransfermechanismus vor.